Biodegradation of absorbable sutures in body fluids and pH buffers - Freudenberg, Sebastian; Rewerk, Stephan; Kaess, Michael; Weiß, Christel; Dorn-Beinecke, A.; Post, Stefan (European surgical research, 2004)
Objective: This study measures the influence of body fluids on the loss of tensile strength of absorbable sutures in vitro. Methods: Nine synthetic absorbable sutures were incubated in different gastrointestinal fluids, as well as in blood and three buffers. Stretch tests were performed after days 0, 7, 14, and 21. Results: Tensile strength varied from 18.5 to 32.8 N, and elasticity varied from 9.5 to 51% of the initial length. The influence of pH, blood, and gastric juice was negligible on all sutures except PDS II®. Except for Monocryl®, all sutures, especially Polysorb® and Vicryl®, lost tensile strength much faster in bile, jejunal and pancreatic juices than in the corresponding buffers. Conclusion: The biodegradation of sutures varies greatly in different body fluids independent of differences in pH.